2013
DOI: 10.3109/14767058.2013.806906
|View full text |Cite
|
Sign up to set email alerts
|

Maternal plasma soluble TRAIL is decreased in preeclampsia

Abstract: Objective Preeclampsia (PE) is characterized by systemic intravascular inflammation. Women who develop PE are at an increased risk for cardiovascular disease in later life. Tumor necrosis factor related apoptosis-inducing ligand (TRAIL) has anti-atherosclerotic effects in endothelial cells and can mediate neutrophil apoptosis. Low soluble TRAIL (sTRAIL) and high C-reactive protein (CRP) concentrations are associated with an increased risk of future cardiovascular disease in non-pregnant individuals. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 200 publications
0
9
0
Order By: Relevance
“…Although the ability of TRAIL to promote spiral artery remodeling is supported by several lines of evidence, there is a paucity of research describing the association between TRAIL and HDP. Chaemsaithong’s [ 28 ] study reported that plasma TRAIL concentrations were significantly lower in patients diagnosed with preeclampsia (22.55 pg/ml) compared to healthy pregnant controls (29.17 pg/ml), suggesting that TRAIL is associated with the pathogenesis of preeclampsia. However, the present study is the first to show that plasma TRAIL levels were decreased before 20 weeks gestation in patients who later developed HDP and were related to HDP (OR = 0.97, P = 0.045).…”
Section: Discussionmentioning
confidence: 99%
“…Although the ability of TRAIL to promote spiral artery remodeling is supported by several lines of evidence, there is a paucity of research describing the association between TRAIL and HDP. Chaemsaithong’s [ 28 ] study reported that plasma TRAIL concentrations were significantly lower in patients diagnosed with preeclampsia (22.55 pg/ml) compared to healthy pregnant controls (29.17 pg/ml), suggesting that TRAIL is associated with the pathogenesis of preeclampsia. However, the present study is the first to show that plasma TRAIL levels were decreased before 20 weeks gestation in patients who later developed HDP and were related to HDP (OR = 0.97, P = 0.045).…”
Section: Discussionmentioning
confidence: 99%
“…Preeclampsia has many features similar to the metabolic syndrome, one of which is the aberrant lipid metabolism [1,[7][8][9]. Since lipid peroxidation plays a role in the development of cardiovascular disease, mothers suffered from preeclampsia are known to have increased risks of cardiovascular disease in their later life [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Since lipid peroxidation plays a role in the development of cardiovascular disease, mothers suffered from preeclampsia are known to have increased risks of cardiovascular disease in their later life [1,8,9]. In addition, circulating free fatty acids (FFAs), known as the key regulators of glucose metabolism, have been shown to increase in preeclamptic patients during and before the clinical onset of the disease [1,7,9]. Since FFAs can become toxic within the cell at high levels, women who develop preeclampsia are at an increased risk for type 2 diabetes in their later life [1,7,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations